Improving Students' Vocabulary Mastery by Using Subtitle Movie - Rahmawaty Mamu; Alan Panigoro; Hasanuddin Fatsah (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
The objective of this research is to find out the students' vocabulary mastery before and after being taught using Indonesian subtitle movies. This research used a quantitative method. Experimental research was applied in this study. The researcher used pre-experimental research to obtain the data. The samples of this research are class C of the English department, class of 2021, consisting of 20 students. The data is obtained by using pre-test, post-test, and treatment. Students are asked to watch the movie in 8 meetings, including pre-test and post-test. To analyze the data, the researcher used a validity test, reliability, paired T-test, and hypothesis verification. The result of this research shows that there are differences between the pre-test and post-test, which means that there was an influence of the use of movies with subtitles on students' vocabulary mastery. In the pre-test, students achieved a score of 65%, while in the post-test, 94%.